Pengaruh Transparansi Anggaran dan Akuntabilitas Keuangan terhadap Kepuasan Masyarakat di Kecamatan Kemalang Kabupaten Klaten Provinsi Jawa Tengah - Anang Tri Wibowo; Eni Dwi Susliyanti (Jurnal Literasi Akuntansi, 2024)
Purpose: This research aims to determine the influence of budget transparency and financial accountability on community satisfaction in Kemalang District, Klaten Regency, Central Java Province. By conducting this research, the researcher hopes that the results of this research can be used as material for evaluation and consideration by the Kemalang District Government in an effort to increase community satisfaction in Kemalang District. Method: This type of research is quantitative research with a total of 111 respondents. This number was obtained using a purposive sampling method. Data collection was carried out using the questionnaire method. The analytical method used is the descriptive analysis method. The measurement tool used to obtain the final research results is the SPSS application Finding: Partial and simultaneous research results show that budget transparency and financial accountability jointly influence community satisfaction in Kemalang District, Klaten Regency, Central Java Province. Novelty: The novelty of this research lies in its location in the Kemalang District of Klaten Regency. This study also included the variable of public satisfaction.